Comparison of cardiac marker profiles in dengue myocarditis - Galang Tri Atmaja; Conroy Surya Wijaya; Annisa Nurul Pratiwi Sudarmadi; Ida Safitri Laksono; Ratni Indrawanti; Eggi Arguni; Sarah Buntubatu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Dengue patients may experience some grade of severity. Cardiac involvement is common in severe dengue, therefore cardiac markers could be used to ensure the diagnosis of dengue myocarditis. However, information of the cardiac marker profiles in patients with milder severity of dengue infection is limited. The study aimed to evaluate creatinine kinase (CK), creatinine kinase-MB (CK-MB) and troponin I (TnI) in dengue myocarditis against the spectrum severity of dengue infection in children. This cross-sectional study was conducted using secondary data from medical records of dengue myocarditis patients aged 1-18 yr in Dr. Sardjito General Hospital, Yogyakarta. Fisher’s Exact tests were performed to compare the increase in cardiac markers to the dengue severity. The increase of CK was observed in dengue fever/DF (6 or 75% of patients), dengue hemorrhagic fever/DHF (6 or 67%) and dengue shock syndrome/DSS (16 or 73%). Furthermore, the increase of CK-MB was also observed in DF (6 or 75%), DHF (8 or 87%), and DSS (21 or 95%). No significant difference in the increase of CK and CK-MB proportions was observed in DF compared to DHF groups and in DF compared to DSS (p>0.05). The increase of Tn I was observed in DHF (2 or 22%) and DSS (10 or 45%) groups but not observed in DF group. Significant difference in the increase of Tn I proportion was observed in DF compared to DSS groups (p=0.022). In conclusion, cardiac involvement is common in all dengue severity level. The increment of Tn I corresponds to an increase in the dengue severity level. Further research by observing cardiac markers sequentially is needed.